Sharia Economics Students' Understanding Of The Prohibition Of Riba In Conventional Bank Institutions - Sutono Sutono (Cakrawala Repositori IMWI, 2024)
The aim of this research is to determine the understanding of sharia economics students regarding the prohibition of usury in conventional banking institutions. Where in Islamic teachings, usury is strictly prohibited according to the guidelines of the Al-Qurana and Al-Hadith. This research uses qualitative research with in-depth interview methods. Data taken from respondents from sharia economics students in the first semester of STAI Kuningan. The results of the research show that sharia economics students really understand about usury because they have often heard what usury is before. Students also understand the practice of usury which is the same as the interest system used by conventional banking institutions. Usury is very detrimental to one of the parties to the transaction. It is not mutually beneficial for the parties carrying out the transaction.